Aflatoxin–albumin adducts and correlation with decreased serum levels of vitamins A and E in an adult ghanaian population - Tang, L.; Xu, L.; Afriyie-Gyawu, E.; Liu, W.; Wang, P.; Tang, Y.; Wang, Z.; Ankrah, N.A.; Huebner, H.J.; Ofori-Adjei, D.et.al (Food Additives and Contaminants - Part A Chemistry, Analysis, Control, Exposure and Risk Assessment, 2009)
A study of aflatoxin (AF) exposure and the levels of vitamins A and E was carried out with a group of 507 Ghanaian participants. AFB1–albumin adducts (AFB-AA) were measured by radioimmunoassay and vitamins A and E were measured by high-performance liquid chromatography (HPLC). The average level of serum AFB-AA was 0.94 ± 0.64 (range = 0.1–4.44) pmol mg−1 albumin. Mean levels of vitamins A and E were 1.32 ± 0.48 (range = 0.41–4.85) µmol l−1 and 15.68 ± 4.12 (range = 6.35–30.40) µmol l−1, respectively. A significantly negative correlation was found between serum AFB-AA and vitamin A levels (r = −0.110, p = 0.013). An even stronger, significant negative, correlation was found between serum AFB-AA and vitamin E levels (r = −0.149, p < 0.001). Serum AFB-AA levels were statistically higher (median = 0.985 pmol mg−1 albumin) in subjects who had low levels of both vitamins A and E as compared with the levels (median = 0.741 pmol mg−1 albumin) subjects who had high vitamins A and E levels (p trend = 0.001). To verify these findings, blood samples were again collected from 165 of the 507 people 3 months after the initial collection. Significantly negative correlations were confirmed between levels of serum AFB-AA and both vitamins A (r = −0.232, p = 0.003) and E (r = −0.178, p = 0.023). Again, high serum AFB-AA concentrations (median = 1.578 pmol mg−1 albumin) were found in subjects with low levels of vitamins A and E compared with the concentrations (median = 1.381 pmol mg−1 albumin) in subjects with high levels of vitamins A and E (p trend = 0.002). These data show that AF exposure was associated with decreased levels of serum vitamins A and E in high-risk human populations, which may significantly influence the incidence of AF-related adverse health effects. © 2009 Taylor & Francis Group, LLC.
Keywords: Aflatoxin-albumin adducts; Aflatoxins; Ghanaian; Vitamin A; Vitamin E